Minimizing the risk of Alzheimer's disease - Murray, Frank, 1924- (Algora Publishing, 2012)
Alzheimer's disease and dementia--which can begin in the 30s--are on the increase, and may soon overwhelm our health-care systems. Yet individuals can do much to educate themselves and learn how to minimize their risks. A prudent diet, lifestyle modifications, nutritional supplements, exercise and activities to stimulate the brain are some of the best ways to prevent or delay Alzheimer's disease. Use your brain or lose it! That's all easy to say, but how scientific are these admonitions and how do we change our habits, anyway? Vitamins, minerals and food supplements are discussed in relation to memory and other functions, as well as an overview of medications, the effects of wine, and the dangers of smoking. The appendices present helpful data to assist in decision-making regarding nursing homes, statistics for Alzheimer's state by state, and a list of support organizations worldwide.